Management of Regional Property in Tomohon City Government - Saeh, Allan Iwan Hendrik; Masengi, Evi Elvira; Mokat, Jetty (Technium Social Sciences Journal, 2023)
Regional Property is one of the important elements in the administration of government and services to the community. Therefore, Regional Apparatus Organizations need to manage Regional Property properly. This study aims to describe and analyze the process of preparing Regional Property Requirement Plans (RKBMD) by Regional Apparatuses in Tomohon City. This study used qualitative research methods. The research locations were 4 (four) regional apparatuses, namely the Regional Health Office of Tomohon City, the Regional Office of Education and Culture of Tomohon City, East Tomohon District, and the Regional Property Management Sector of the Regional Revenue and Financial Management Agency of Tomohon City. The focus of the research is how the implementation of the Minister of Home Affairs Regulation concerning the Management of Regional Property in the process of preparing the Plan for Requirements for Regional Property (RKBMD), especially Equipment and Machinery from 4 (Four) Regional Apparatus Organizations within the Tomohon City Government. the management of regional property in the Tomohon City Government, in this case, the preparation of the Regional Property Needs Plan (RKBMD) in the Tomohon City Government, has not gone well. This is because the 4 (four) aspects studied, explain that the main obstacle in the communication aspect is socialization when viewed from the main resource aspect it can be concluded that the lack of human and budgetary resources is an obstacle in the resource aspect, and in aspects of disposition can be seen from the lack of awareness in carrying out responsibilities as regional property management officials and on aspects of the bureaucratic structure where the lack of understanding of SOPs regarding the preparation of Regional Property Needs Plans (RKBMD).